ChemInform Abstract: Catalyst‐Free Three‐Component Tandem CDC Cyclization: Convenient Access to Isoindolinones from Aromatic Acid, Amides, and DMSO by a Pummerer‐Type Rearrangement. Issue 36 (August 2016) - Wang, Peng‐Min; Pu, Fan; Liu, Ke‐Yan; Li, Chao‐Jun; Liu, Zhong‐Wen; Shi, Xian‐Ying; Fan, Juan; Yang, Ming‐Yu; Wei, Jun‐Fa
Abstract: A catalyst free three‐component reaction of 3, 4, 5‐trimethoxybenzoic acid with sulfonamides or carboxylic amides and DMSO as methylene source proceeds through a Pummerer‐type rearrangement to provide a convenient access to N‐substituted isoindolinones.